The Influence of Brand Image, Product Quality, and Price on Customer Satisfaction (A Study at Warung Seblak Neng Otot, Garut Regency) - Kusnadi, Agung Akhmad Gumelar; Sirait, Tongam (Riviera Publishing, 2025)
This study aims to analyze the influence of brand image, product quality, and price on customer satisfaction at Warung Seblak Neng Otot in Garut Regency. The research background is based on the rapid growth of the spicy culinary business, especially Seblak, as well as the importance of differentiation through effective marketing strategies. This study uses a quantitative approach with a survey method through a questionnaire administered to 200 respondents. The data were analyzed using validity, reliability, exploratory factor analysis (EFA), and multiple linear regression tests, complemented by classical assumption tests. The results showed that simultaneously, brand image, product quality, and price had a significant effect on customer satisfaction (R² = 0.684). However, partially, only brand image and price had a significant effect, while product quality did not. Brand image had the most dominant influence (? = 0.452), followed by price (? = 0.333). These findings confirm the importance of building a strong brand perception and setting prices commensurate with the product's value in creating customer satisfaction, especially in the competitive culinary MSME sector. The practical implications of this research encourage business actors to focus on strengthening brand identity and value-based pricing strategies as the key to long-term success.